A revision of the Cretaceous ant genus Zigrasimecia Barden & Grimaldi, 2013 (Hymenoptera: Formicidae: †Zigrasimeciinae) - Chaul, Júlio Cezar Mário (Zootaxa, 2023)
The extinct Cretaceous ant genus Zigrasimecia Barden & Grimaldi, the “iron maiden ants” from Myanmar, is revised, and five new species are described: †Z. boudinoti sp. nov., †Z. caohuijiae sp. nov.,†Z. chuyangsui sp. nov., †Z. perrichoti sp. nov., and †Z. thate sp. nov. Zigrasimecia hoelldobleri paratype (CNU-HYM-MA2019054) is removed from the type series. New diagnoses for all species are provided and species boundaries are discussed. Studied specimens that are not ideally preserved are presented and discussed, some of them are putative new species. Two identification keys for the genus are provided, a traditional, dichotomous key and an interactive, multi-entry key hosted online at the website www.Xper3.fr. I briefly discuss the unlikeliness of the genus Boltonimecia to belong to the subfamily Zigrasimeciinae, and also the taxonomic problem caused by the description of species based on alates and poorly preserved fossils.